Remote multiparametric monitoring and management of heart failure patients through cardiac implantable electronic devices - Boriani, Giuseppe; Imberti, Jacopo F.; Bonini, Niccolò; Carriere, Cosimo; Mei, Davide A.; Zecchin, Massimo; Piccinin, Francesca; Vitolo, Marco; Sinagra, Gianfranco (European journal of internal medicine, 2023)
•Heart failure (HF) is associated with a substantial risk of hospitalizations and adverse outcomes.•In patients with cardiac implantable electronic devices (CIEDs) there is the possibility of multiparametric remote monitoring of HF.•Several CIEDs parameters may result in multiparametric scores predicting patients’ risk of worsening HF.•Patients can be managed days or weeks before overt decompensation, at the time of CIEDs pre-clinical alerts.•Decision making on clinical, laboratory or instrumental checks is needed in order to assess the need for escalating HF medications after a remote monitoring alert. In this review we focus on heart failure (HF) which, as known, is associated with a substantial risk of hospitalizations and adverse cardiovascular outcomes, including death. In recent years, systems to monitor cardiac function and patient parameters have been developed with the aim to detect subclinical pathophysiological changes that precede worsening HF. Several patient-specific parameters can be remotely monitored through cardiac implantable electronic devices (CIED) and can be combined in multiparametric scores predicting patients’ risk of worsening HF with good sensitivity and moderate specificity. Early patient management at the time of pre-clinical alerts remotely transmitted by CIEDs to physicians might prevent hospitalizations. However, it is not clear yet which is the best diagnostic pathway for HF patients after a CIED alert, which kind of medications should be changed or escalated, and in which case in-hospital visits or in-hospital admissions are required. Finally, the specific role of healthcare professionals involved in HF patient management under remote monitoring is still matter of definition. We analyzed recent data on multiparametric monitoring of patients with HF through CIEDs. We provided practical insights on how to timely manage CIED alarms with the aim to prevent worsening HF. We also discussed the role of biomarkers and thoracic echo in this context, and potential organizational models including multidisciplinary teams for remote care of HF patients with CIEDs.